The Effect of The Application of The Realistic Mathematucs Education (RME) Learning Model on Chritical Thingking Ability - Sripatmi; Hadiawati, Titin; Kurniawan, Eka; Hayati, Laila (Balai Publikasi Indonesia, 2024)
This research aimed to determine the effect of the Realistic Mathematics Education (RME) learning model on students critical thinking ability for systems of linear equations with two variabels material in class VIII at SMP Negeri 3 Jerowaru for the academic year 2023/2024. Research with a quantitative approach that uses a quasi-experimental design, the experimental class learning using the RME learning model while the control class using direct learning. The population in this study was 3 class VIII students. The samples were taken using a simple random sampling technique, resulting in class VIII A as the experimental class and VIII B as the control class. Data collection was carried out using critical thinking ability test questions (posttest). From the research results, it was found that there were differences between the experimental class and the control class. Judging from the average score of the experimental class 69.08 and the control class 58.40, this shows that the critical thinking ability of the class whose learning uses RME is better than the class whose learning uses direct learning. The effect size test results obtained were 0.69, which is in the medium category. So it can be concluded that there is an effect of the RME learning model on students' critical thinking skills in SPLDV material in class VIII of SMP Negeri 3 Jerowaru in the medium category. Keywords: Realistic Mathematics Education (RME) Learning Model, Critical Thingking Ability, Systems of Linear Equations with Two Varabels